The Amish veil: Symbol of separation and community - Hawley, Jana M. (University of California Press, 2008)
Veiling has existed in countless cultures and religions from time immemorial. Today, veiling is a globally polarizing issue between contemporary and traditional cultures. For the Amish, veiling comes in two forms, the prayer cap and the bonnet and also serves as a visual separator and identifier. Amish dress varies by community and is based on local conventions called the Ordnung. These subtle, but specific rules parallel the rest of the community's relative level of progressiveness. Amish tenets expect Amish women to have their heads covered in public at all times. This article shares the insights of Amish culture and dress practices in a Midwest Amish community.
Keywords: Old order Amish; Veiling; Culture; Anthropology; Sociology; Dress